The effect of Meranti Merah wood fiber loading and sizes to the absorption property of polymer foam composites - Zaliran, Muhammad Taufiq (2018)
As the problem of undesirable and potentially hazardous noise has become serious, the demand of better environment is increased and becomes a major requirement. Acoustical material which plays important roles in acoustic engineering. Polymer foam composites (PFC) were developed for absorption material based on epoxy, renewable monomer from waste cooking oil, isocyanates and wood fiber fillers. The polymer foam composite (PFC) were fabricate based on four percentages of wood fiber filler loading which are 5, 10, 15, and 20 wt% ratio ofpolyol for two types size ofMeranti Merah (MM) in powder and flakes form. A set of samples for sample tube 100 mm diameter for low frequency of 0 to 1500 Hz, while the small sample tube of 28 mm diameter is to measure the high frequency absorption level of 1500 to 6000 Hz. Furthermore, the samples were irradiated in ultra violet exposure in the UV Weatherometer to examine the stability of the PFC. Meanwhile, three different thickness ofPFC that is 10 mm, 20 mm and 30 mm were also tested in impedance tube test for its acoustic property. The result revealed that the higher wood filler loading and higher the thickness of polymer foam, the higher the sound absorption coefficient (a). The morphological pores structures show slightly decrease in sizes due to the increasing fiber filler loading while the pores structures show slightly increased on increasing UV irradiation exposure hours. It is therefore revealed that the polymer foam composite (PFC) whether based from epoxy (E) renewable monomer (RM) with different percentage loading of fiber filler as well as different thickness shows remarkable characteristic of sound absorption coefficient. The highest sound absorption coefficient (SAC) is 0.999 for sample EFzo30 while the lowest SAC is 0.600 for sample RM at different frequency absorption levels. It is best to conclude that, the higher percentage loading of fiber flakes filler as well as the highest thickness of foams revealed the most promising characteristic of sound absorption material, thus suggesting the optimum composition ratios of fiber filler at 30 % wt.